Putting enterprise to work - the Jamaican divestment experience. - Stone, Carl (1992)
Reports on the performance of 162 of 202 divested entities in Jamaica. Assesses whether divestment made a difference in the management and performance of the divested enterprises. Notes that public opinion continues to be ambivalent about divestment.